Befores & Afters Magazine - Failes, Ian, ....- (S.l. : s.n., 2022)
Inside issue #4 of befores & afters magazine: - the history of CG birds in visual effects - hand-drawn effects animation on Ghostbusters II - in-camera VFX - looking back at the VFX of Independence Day - Douglas Trumbull, in pictures
Keywords: Animation; Visual effects